Leadership and the Money Politics Trap in Islamic Legal Thought: A Case Study of Indonesia as a Muslim-Majority Country - Fernando, Henky; Larasati, Yuniar Galuh; Abdullah, Irwan; Horakova, Hana (Nurani, 2024)
This study aims to evaluate the attitudes of leaders shaped after being trapped in the practice of money politics by voters in general elections based on Islamic law. This context tends to be overlooked by previous studies discussing the issue of money politics in elections. In addition to responding to the shortcomings of previous studies, this study also focuses on evaluating the characteristics and implications of money politics in shaping leaders' attitudes post-election based on Islamic law. This study employs a qualitative descriptive approach based on Islamic law to explore the characteristics, factors, and implications of money politics on leaders' attitudes post-election. The findings of this study reveal three important contexts regarding the characteristics of money politics in elections in Indonesia that contradict Islamic law. First, the practice of money politics in elections often appears in the form of cash payments, digital money, and the provision of projects with political aims. Second, money politics practiced in elections is frequently influenced by structural, cultural, and infrastructural factors oriented towards transactional politics. Third, the money politics conducted by actors in the elections has shaped opportunistic, pragmatic, and even corrupt attitudes among leaders post-election.